2021
DOI: 10.1038/s41598-021-87830-7
|View full text |Cite
|
Sign up to set email alerts
|

Probability of severe postpartum hemorrhage in repeat cesarean deliveries: a multicenter retrospective study in China

Abstract: To determine the factors predicting the probability of severe postpartum hemorrhage (SPPH) in women undergoing repeat cesarean delivery (RCD). This multicenter, retrospective cohort study involved women who underwent RCD from January 2017 to December 2017, in 11 public tertiary hospitals within 7 provinces of China. The all-variables model and the multivariable logistic regression model (pre-operative, operative and simple model) were developed to estimate the probability of SPPH in development data and extern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…We think that may be related to the amount of RBC transfusion is one of the outcomes of SPPH and the influence of HGB concentration on coagulation function (19,20). The PB, AP, PP, number of prior CDs, and PAS in the nomogram were similar to the existing models (9)(10)(11)(12) and other research (21,22). More information about the existing models for predicting the risk of SPPH for women with PP is shown in Appendix Table 5.…”
Section: Discussionsupporting
confidence: 52%
“…We think that may be related to the amount of RBC transfusion is one of the outcomes of SPPH and the influence of HGB concentration on coagulation function (19,20). The PB, AP, PP, number of prior CDs, and PAS in the nomogram were similar to the existing models (9)(10)(11)(12) and other research (21,22). More information about the existing models for predicting the risk of SPPH for women with PP is shown in Appendix Table 5.…”
Section: Discussionsupporting
confidence: 52%
“…Mothers presented with previous CS scar ≥ 2 were 4.08 times more likely to have severe PPH when compared to mothers with one and no cesarean scar. Findings from other studies 7 , 26 , 27 also revealed that the likelihood of developing severe PPH is significantly higher in mothers with the previous scar than in their counterparts. This indicates that the presence of CS scar might predispose them to significant bleeding and uterine atony due to the formed adhesion and increased risk of abnormal placentation.…”
Section: Discussionmentioning
confidence: 66%
“…Amongst studies specifically evaluating predictors for severe PPH after CD 24 , 26 28 , previous CS scar 26 , 27 , antepartum hemorrhage 24 , 27 , multiple pregnancies 23 , 28 , preeclampsia 3 , general anesthesia 23 , 24 , 28 , antepartum anemia 27 , 28 and maternal age ≥ 35 years 3 are reported as potential predictors; however, PPH may also occur in some women with no known risk factors 4 .…”
Section: Introductionmentioning
confidence: 99%
“…The decision curve of a model is compared with extreme cases that include all patients or none. A model can be recommended for clinical use if its net benefit is greater than treating all and no patients (Du et al, 2021 ). Comparing the result of Model 1 with Model 2, the two models were both better than extreme cases (none and all) in the test set.…”
Section: Discussionmentioning
confidence: 99%